Differential pulse voltammetric determination of homovanillic acid as a tumor biomarker in human urine after hollow fiber-based liquid-phase microextraction - Hrdlička, Vojtěch; Barek, Jiří; Navrátil, Tomáš (Talanta, 2021)
Novel method for the determination of a tumor marker homovanillic acid (HVA) in human urine was developed. Combination of hollow fiber - based liquid-phase microextraction (HF-LPME) and differential pulse voltammetry (DPV) at a cathodically pre-treated boron doped diamond electrode (BDDE) was applied for these purposes. Optimum conditions were: butyl benzoate as supported liquid membrane (SLM) formed on polypropylene HF, 0.1 mol L-1 HCl as donor phase, 0.1 mol L-1 sodium phosphate buffer of pH 6 as acceptor phase, and 30 min extraction time. HF-LPME-DPV concentration dependence was linear in the range from 1.2 to 100 μmol L-1. Limits of quantification (LOQ) and detection (LOD) were 1.2 and 0.4 μmol L-1, respectively. The applicability of the developed method was verified by analysis of human urine. Standard addition method was used, found HVA concentration was 13.5 ± 1.3 μmol L-1, RSD = 9.3% (n=5).
Keywords: Liquid Phase Microextraction; kyselina homovanilová; vysokoúčinná kapalinová chromatografie; Homovanillic Acid; Biomarkers, Tumor; lidé; Chromatography, High Pressure Liquid; nádorové biomarkery; mikroextrakce kapalné fáze; Humans